Proceedings of the EMNLP 2014 Workshop on Arabic Natural Language Processing (ANLP) 2014
DOI: 10.3115/v1/w14-3623
|View full text |Cite
|
Sign up to set email alerts
|

A Large Scale Arabic Sentiment Lexicon for Arabic Opinion Mining

Abstract: Most opinion mining methods in English rely successfully on sentiment lexicons, such as English SentiWordnet (ESWN). While there have been efforts towards building Arabic sentiment lexicons, they suffer from many deficiencies: limited size, unclear usability plan given Arabic's rich morphology, or nonavailability publicly. In this paper, we address all of these issues and produce the first publicly available large scale Standard Arabic sentiment lexicon (ArSenL) using a combination of existing resources: ESWN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 14 publications
0
112
0
Order By: Relevance
“…These features performed well after reduction via the Entropy-Weighted Genetic Algorithm (EWGA) (Abbasi et al, 2008). Sentiment lexicons also provided an additional source of features that proved useful for the task (Abdul-Mageed et al, 2011;Badaro et al, 2014;.…”
Section: Related Workmentioning
confidence: 99%
“…These features performed well after reduction via the Entropy-Weighted Genetic Algorithm (EWGA) (Abbasi et al, 2008). Sentiment lexicons also provided an additional source of features that proved useful for the task (Abdul-Mageed et al, 2011;Badaro et al, 2014;.…”
Section: Related Workmentioning
confidence: 99%
“…They [12] produced the first publicly available large scale Standard Arabic sentiment lexicon (Ar-SenL) using a combination of existing resources: English WordNet (EWN), Arabic Word-Net (AWN 2.0), English SentiWordNet (ESWN 3.0) and the Standard Arabic Morphological Analyzer (SAMA 3.1) [13]. They showed that using English-based linking produces, on average, superior performance in comparison to using the WordNet-based approach.…”
Section: Lexicon Building Of Other Languagesmentioning
confidence: 99%
“…We followed the setup proposed by (Al Sallab et al, in press 2017) by applying RAE to morphologically tokenized text which proved to improve the performance by reducing the lexical sparsity of the language. We also use a broader semantic representation of words by concatenating word embeddings trained using the skip-gram model (Mikolov et al, 2013) with sentiment embeddings trained using the ArSenL sentiment lexicon (Badaro et al, 2014).…”
Section: System 3: Recursive Auto Encodersmentioning
confidence: 99%
“…and achieved good performances after applying the EntropyWeighted Genetic Algorithm for feature reduction (Abbasi et al, 2008). Sentiment lexicons also provided an additional source of features that proved useful for the task (Abdul-Mageed et al, 2011;Badaro et al, 2014 A framework was developed for tweets written in Modern Standard Arabic (MSA) and containing Jordanian dialects, Arabizi (Arabic words written using Latin characters) and emoticons. This framework was realized by training different classifiers using features that capture the different linguistic phenomena (Duwairi et al, 2014).…”
Section: Related Workmentioning
confidence: 99%